Automatic summarization of web documents - Jodihardja, Marcellus Reinaldo (2013)
Nowadays, we face an information overload, with all the rapid development in R& D and technological advancement. Even though information overload means that we can have various information regarding a specific topic, but it start to became more difficult to retrieve all the information needed in a limited time.